RANCANG BANGUN ALAT PENGADUK BUBUR OTOMATIS MENGGUNAKAN SENSOR SUHU BERBASIS ARDUINO UNO - Thamrin Thamrin; Delsina Faiza; Ilmiyati Rahmy Jasril (Universitas Negeri Padang, 2017)
The aim of this research is to design and make stirring tool of corn grits with rotation speed of stirring based on temperature rise level detected by temperature sensor. Arduino Uno as reader of input data from temperature sensor and set output in the form of motor rotation stirrer, LCD display and buzzer. The benefits of this research in the field of application of electronics sensors in food processing, especially the effective and efficient corn grits processing. Both in terms of time, cost, energy and safety. Keywords: Designing, Stirring, Corn Grits, Arduino Uno, Sensor